Monolog Kebangkitan (Tanpa Suara): Analisis Pendekatan Budaya Resepsi Sastra - Karmila br Karo; Reza Pahlevi Ginting (Departement of Mathematics Education, 2023)
This study aims to analyze a drama monologue of awakening using a literary reception approach. Literary reception is a literary genre that examines literary texts by considering the reader as the giver of speech or response. This research refers to the understanding and assessment given by the audience towards the drama